Academic Interventions Promoting Learner's Success in Secondary Schools under King Cetshwayo District, South Africa - Mahaye, Ngogi Emmanuel (International Journal of Humanity and Social Sciences, 2024)
Purpose: This study was a phenomenological study designed to make decisions using information from participants' experiences. The purpose of the study was to develop a model which can be used to improve teaching and learning in rural secondary schools. Success oriented policies developed by SMT was studied. The contribution of efficient Students Representative Councils towards academic improvement in rural secondary schools was also studied. Methodology: The study is underpinned by qualitative approach, interprevist paradigm, and exploratory design. Participants for the study were chosen by purposive sampling. Four rural secondary schools in King Cetshwayo district (KCD) were selected for study. Two out of the four schools were well performing schools while the other two were underperforming schools. Performance was based on pass rate in the NCS examination. Principals, deputy principals, some HODs and some learners were selected as participants for that study. Semi-structured interviews were conducted using research interview schedule tool. Findings: Data collected from participants' response were analyzed per school and comparisons drawn between schools. Most participants appreciated academic interventions, although raised sentiments of some arriving very late. Study reveals that the performance did increase after those interventions. Unique Contribution to the theory, practice, and policy: Conclusions were drawn from the results. A model for academic improvement was developed using results obtained from the data analysis and underpinned by the theory of Concerned Base Adoption Model (CBAM). The model can be used by underperforming schools to improve learner success.